Characterization of Abandoned Mine Voids Under Roadway with Land-Streamer Seismic Waves. Issue 1 (2016) - Sullivan, Brian; Tran, Khiem T.; Logston, Brian
The paper presents an application of two-dimensional (2-D) time-domain waveform tomography for characterization of abandoned underground mine voids under a highway. Measured surface-based seismic wave fields are inverted by a full waveform inversion technique that is founded on a finite-difference solution of 2-D elastic wave equations and the Gauss–Newton inversion method. The key advantage of this waveform approach is the ability to generate all possible wave propagation modes of seismic wave fields (body waves and Rayleigh waves) by forward modeling; the modes are then compared with measured data to infer complex subsurface properties. Both the pressure wave and shear wave velocities are inverted independently and simultaneously to increase the credibility of characterized profiles. Real experimental data sets were collected on asphalt pavement by using a land streamer, which did not require that geophones be coupled into the pavement and allowed the testing system to be moved along the road quickly. The seismic results show that the waveform analysis was able to delineate two mine voids embedded at a depth of about 15 m. The existence of the voids was confirmed by confirmation drilling.